A Diagnostic Dilemma: Bosniak III Renal Cyst and Missed Papillary Urethral Lesion – A Case Report - Hussain, Nabeel Umer; Hassan, Farah; Habeeb, Amer (Biological and Clinical Sciences Research Journal, 2025)
Renal cysts are common findings in clinical practice, with the Bosniak classification system guiding management based on imaging characteristics. Bosniak III cysts, characterised by multiple septations and enhancing walls, present a challenge due to their intermediate malignancy risk. This case report describes a 47-year-old male with a complex left renal cyst initially classified as Bosniak III in Qatar but later downgraded to Bosniak IIF in the United Kingdom, leading to surveillance rather than immediate surgical intervention. Additionally, a papillary growth in the prostatic urethra was missed during initial evaluations. This case highlights the importance of expert multidisciplinary team (MDT) discussions, imaging standardisation, and thorough urological assessments in patients presenting with hematuria and renal cystic lesions.